Validated Immunosorbent Surface-Based Determination of Theophylline in Milk - (:unkn) unknown (PLEIADES PUBLISHING INC, 2020)
In the present study, an immunosorbent surface-based theophylline determination method was developed and validated. The procedure was tested on milk samples. Theophylline was removed from milk by an immunosorbent surface. The efficiency of theophylline removal was found to be between 95-97%. The proposed method is cost effective and does not require any special equipment. Detection and quantification limits of the proposed method were determined based on the standard deviation of 10 ng/mL theophylline and they were equal 3 and 11 ng/mL, respectively. Results were also validated for precision, accuracy and linearity.
Keywords: immunosorbent surface; theophylline; milk; spectroscopy; CAFFEINE; THEOBROMINE; QUANTIFICATION; ALKALOIDS; PLASMA; DRINKS; FOOD